Pemanfaatan Mulsa Jerami dan Plant Growth Promoting Rhizobacteria untuk Menekan Penyakit Pustul Bakteri pada Tanaman Kedelai - Tita Widjayanti; Abdjad Asih Nawangsih; Kikin Hamzah Mutaqin (Jurnal Fitopatologi Indonesia, 2012)
Bacterial pustule caused by Xanthomonas axonopodis pv. glycines is one of important bacterial diseases of soybean in Indonesia. The development of alternative control of the disease is required to support integrated diseases management for sustainable agriculture. This research was conducted to observe the effect of straw mulch and plant growth promoting Rhizobacteria (PGPR) on the incidence of bacterial pustule disease on two soybean varieties in the farmer field at Cigombong, Sukabumi, West Java. The result of this research showed that all of the factors as combinations did not significantly affect the value of total area under disease progress curve (AUDPC) of bacterial pustule. Factor that significantly affected the values of AUDPC was soybean varieties. Gepak Kuning variety has lowest AUDPC value compared to Anjasmoro variety. In addition, combination of Gepak Kuning variety and straw mulch showed significantly different effect on AUDPC value. Therefore, this treatment combination should be recommended for the farmers.Key word: PGPR, soybean variety, straw mulch, Xanthomonas axonopodis pv. glycines